2013
DOI: 10.1002/grl.50326
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide ice clouds, snowfalls, and baroclinic waves in the northern winter polar atmosphere of Mars

Abstract: The formation of CO2 ice clouds in the northern winter polar atmosphere of Mars and their relation to baroclinic planetary waves, which dominate local dynamics, are studied using a general circulation model. The simulation shows that clouds are formed at altitudes of up to ∼ 40 km, and their occurrence correlates to a large degree with the cold phases of transient planetary waves. Ice particles formed up to ∼ 20 km can reach the surface in the form of snowfall in certain longitude regions, while in others, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
(55 reference statements)
4
32
0
Order By: Relevance
“…The MGCM employs the spectral dynamical core of the Model for Interdisciplinary Research On Climate terrestrial GCM, which was developed collaboratively by the Atmosphere and Ocean Research Institute, The University of Tokyo, the National Institute of Environmental Studies, and the Japan Agency for Marine‐Earth Science and Technology in Japan (K‐1 Model Developers, ; Sakamoto et al, ). The implemented physical parameterizations suitable for the Martian atmosphere have been described in detail in the works by Kuroda et al (, ). The lower‐resolution version of the MGCM has been validated against the observed zonal mean climatology (Kuroda et al, ) and applied for studies of baroclinic planetary wave activity (Kuroda et al, ), annular mode variability in the middle and high latitudes (Yamashita et al, ), equatorial semiannual oscillations (Kuroda et al, ), winter polar warmings during dust storms (Kuroda et al, ), and CO 2 snowfalls during northern polar winters (Kuroda et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MGCM employs the spectral dynamical core of the Model for Interdisciplinary Research On Climate terrestrial GCM, which was developed collaboratively by the Atmosphere and Ocean Research Institute, The University of Tokyo, the National Institute of Environmental Studies, and the Japan Agency for Marine‐Earth Science and Technology in Japan (K‐1 Model Developers, ; Sakamoto et al, ). The implemented physical parameterizations suitable for the Martian atmosphere have been described in detail in the works by Kuroda et al (, ). The lower‐resolution version of the MGCM has been validated against the observed zonal mean climatology (Kuroda et al, ) and applied for studies of baroclinic planetary wave activity (Kuroda et al, ), annular mode variability in the middle and high latitudes (Yamashita et al, ), equatorial semiannual oscillations (Kuroda et al, ), winter polar warmings during dust storms (Kuroda et al, ), and CO 2 snowfalls during northern polar winters (Kuroda et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The implemented physical parameterizations suitable for the Martian atmosphere have been described in detail in the works by Kuroda et al (, ). The lower‐resolution version of the MGCM has been validated against the observed zonal mean climatology (Kuroda et al, ) and applied for studies of baroclinic planetary wave activity (Kuroda et al, ), annular mode variability in the middle and high latitudes (Yamashita et al, ), equatorial semiannual oscillations (Kuroda et al, ), winter polar warmings during dust storms (Kuroda et al, ), and CO 2 snowfalls during northern polar winters (Kuroda et al, ). Recently, this model has been used for validating the temperature retrievals from the MGS radio occultations during the southern polar night (Noguchi et al, ), studying modulation of CO 2 clouds by stationary and transient waves (Noguchi et al, ), and exploring the influence of a global dust storm on the electron densities in the D region of the ionosphere (Haider et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These form in both the Northern and Southern Hemispheres during their respective winters and are an important barrier for the mixing of polar and midlatitude air. As such, they act to intensify meridional temperature gradients, influence the rate of condensation of CO 2 onto the polar ice cap, and limit the transport of dust and ice aerosols toward polar regions (Colaprete et al 2008;Kuroda et al 2013;Guzewich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the occurrence of condensation was very variable, even at the same latitudes in the northern hemisphere, attributing the northern seasonal variation in CO 2 condensation to multiple meteorological events, including the development of baroclinic waves. More detailed analyses for the relationship between transient waves and CO 2 supersaturation using observational data are needed to confirm the results suggested in Hu et al [] and Kuroda et al [].…”
Section: Introductionmentioning
confidence: 99%
“…Barnes [2006] and Barnes et al [2009] suggested that transient waves cause CO 2 condensation in the atmosphere. The results of a Martian General Circulation Model (MGCM) showed that baroclinic waves cause CO 2 supersaturation and condensation, which results in CO 2 clouds and even snowfall in the northern winter polar atmosphere [Kuroda et al, 2013]. Hu et al [2012] is a comprehensive study of CO 2 condensation on Mars.…”
Section: Introductionmentioning
confidence: 99%